Application of Economic Order Quantity (EOQ) and Economic Production Quantity (EPQ) Methods to Realize the Efficiency of Raw Material Inventory Costs - Setiana, Cindy; Budiana, Deni (Almana : Jurnal Manajemen dan Bisnis, 2025)
The research on the Fish Meatballs CV. Sinar Bahari Indonesia highlights that they currently order raw materials using traditional methods based on estimates, without employing the Economic Order Quantity (EOQ) or Economic Production Quantity (EPQ) methods. This leads to ineffective control of fish raw materials and high total inventory costs. Implementing the EOQ method can improve inventory cost management by saving on ordering, storage, and shortage costs. Similarly, applying the EPQ method can enhance production cost efficiency by optimizing the order quantity based on production needs. Using these methods can result in significant savings and more effective control of inventory costs for the company.